1994
DOI: 10.1084/jem.180.3.1141
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of vascular permeability factor/vascular endothelial growth factor and its receptors in psoriasis.

Abstract: SummaryPsoriatic skin is characterized by microvascular hyperpermeability and angioproliferation, but the mechanisms responsible are unknown. We report here that the hyperplastic epidermis of psoriatic skin expresses strikingly increased amounts of vascular permeability factor (VPF; vascular endothelial growth factor), a selective endothelial cell mitogen that enhances microvascular permeability. Moreover, two VPF receptors, kdr and fit-l, are overexpressed by papillary dermal microvascular endothelial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
452
1
11

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 632 publications
(484 citation statements)
references
References 41 publications
20
452
1
11
Order By: Relevance
“…Overexpression of VEGF has been reported in skin disorders that are characterized by angiogenesis and increased vascular permeability (Brown et al, 1995a). VEGF is strongly expressed by epidermal keratinocytes in wound healing and psoriasis, both accompanied by angiogenesis and increased microvascular permeability (Brown et al, 1992;Detmar et al, 1994). In delayed hypersensitivity skin reactions, which are also characterized by microvascular hyperpermeability, in situ hybridization revealed that the mRNAs encoding VEGF were strikingly overexpressed in keratinocytes of the epidermis (Brown et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of VEGF has been reported in skin disorders that are characterized by angiogenesis and increased vascular permeability (Brown et al, 1995a). VEGF is strongly expressed by epidermal keratinocytes in wound healing and psoriasis, both accompanied by angiogenesis and increased microvascular permeability (Brown et al, 1992;Detmar et al, 1994). In delayed hypersensitivity skin reactions, which are also characterized by microvascular hyperpermeability, in situ hybridization revealed that the mRNAs encoding VEGF were strikingly overexpressed in keratinocytes of the epidermis (Brown et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…6 In adult skin, VEGF expression is almost undetectable under phy- siologic conditions, while its up-regulation occurs in hyperplastic epidermis of healing wounds 7 and psoriatic skin. 8 VEGF is a potent mitogen for dermal microvascular endothelial cells, 9 it is expressed in keratinocytes of healing wounds 10,11 and acts in a paracrine manner on dermal microvessels, leading to increased skin vascularity. 12,13 Recently, the in vivo activity of hVEGF promoter has been shown in wounded transgenic mouse skin.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] VEGF and the pro-angiogenic factors described above appear to function primarily at the level of newly formed vessels where they promote survival by repressing endothelial cell apoptosis. 1 There is mounting evidence that conditions that enhance endothelial cell survival contribute to the pathogenesis of angiogenesis-dependent diseases such as cancer, [8][9][10] psoriasis, 11,12 retinopathy of prematurity, 13 and Crohn's disease. 14 Therefore, reduction or disruption of the local …”
Section: Introductionmentioning
confidence: 99%